Under the same rainbow: A study on homophobia and discrimination among private sector health care professionals. (13th October 2020) - Taskiran Eskici, Gulcan; Alan, Handan; Eskin Bacaksiz, Feride; Gumus, Emel; Cakir, Hanife; Harmanci Seren, Arzu Kader
Abstract: Aim: To determine the homophobic and discriminatory attitudes of health care professionals and associated factors in the private sector. Background: Examining possible homophobic and discriminatory attitudes of health care professionals is very important to eliminate barriers such as access to and use of health services. Method: This descriptive and cross‐sectional study included 626 health professionals in 20 private hospitals throughout Turkey. The data were collected in May 2020 using an online questionnaire containing the Hudson and Ricketts Homophobia Scale and the Discriminatory Attitudes Scale . Results: Most of the health professionals (64.4%) said that they did not know any LGBTQ+ people, almost half (44.2%) had cared LGBTQ+ people before, and most (95.4%) said that they would be willing to care them. The health professionals' homophobia score was 3.60 ( SD  = 1.23), and their discrimination score was 2.10 ( SD  = 0.71). A positive relationship was found between their homophobia and discrimination scores( r  = .642). Significant differences in their scale scores were found to be related to their personal and professional characteristics. Conclusions: The homophobic attitudes of health professionals were above average and had a positive relationship with discriminatory attitudes. Implications for Nursing Management: Private hospital administrators should plan initiatives and training programmes to improve health care professionals' attitudes towards LGBTQ+ people.